ANALYSIS OF IMPLEMENTATION OF SAK EMKM IN SMALL AND MEDIUM MICRO ENTERPRISES (MSMEs) (CASE STUDY ON CV. DICO INTERIOR SURABAYA) - Karlin Karlin; Antoni Antoni (Cross-Border Journal of Business Management, 2021)
Covid 19 has an impact on the national and global economy; this is evidenced by the national economic growth that did not increase, even decreased by 5.3% in the third quarter of 2020. The decline in economic growth was due to a decrease in household consumption due to social restrictions to prevent the spread of covid-19, decrease investment spending for construction and purchase of fixed assets and decrease government spending realization and decrease foreign trade. The problem in this study is how to apply SAK EMKM in the preparation of financial statements and what factors cause SAK EMKM-based financial records not to be implemented. This research was conducted using descriptive research with a qualitative approach. The object of this research is a CV. Dico Interior is engaged in the Interior Design business. The results of this study are 1). The company has made financial statements but has not met the EMKM Financial Accounting Standards. Reports are made more on the Cash Flow Statement and Budget Plan (RAB), which are used to calculate the estimated costs incurred if there is work; 2). The company, in this case, the owner, does not yet know how important financial statements are as a tool to evaluate the company's operations because the owner considers this his own company and does not need to make financial statements correctly; 3). Financial reports that are made are more directed at the Cash Flow report only, without paying attention to other elements in preparing financial statements such as receivables, inventories, and depreciation of Fixed Assets only displays incoming and outgoing money; 4). The owner considers that the financial statements are made only if they require a loan to the bank for additional working capital.